Settlement of Business Contract Disputes through Arbitration Efforts in Civil Law Review - Purnawadi Otoluwa; Osgar Sahim Matompo; Irmawaty (Indonesian Research Journal in Legal Studies, 2022)
This study aims to identify and analyze the principles, procedures, and obstacles in resolving business contract disputes through arbitration. The results of the study found that dispute resolution through arbitration has the principle that the arbitration examination process is carried out in a closed manner, the parties have the same opportunity to have their opinions heard, and the parties are free to determine the arbitration program to be used. The dispute resolution process through arbitration will be carried out according to the rules and procedures of the arbitration institution chosen by the parties. Obstacles in the dispute resolution process through arbitration can come from various parties involved in the dispute resolution process through arbitration, such as arbitrators who are not in proper nature, arbitration institutions that are not widely known by the public, one of the disputing parties has bad faith, it can even come from the interference of the district court in the arbitration award. Research suggestions are that there is a need to provide an understanding of the principles and procedures for resolving disputes through arbitration, it is necessary to have awareness from the parties concerned so that the dispute resolution process through arbitration can produce a win-win solution or so that the parties to the dispute get a mutual settlement and benefit the parties who are in dispute.